2010
DOI: 10.1093/ije/dyq168
|View full text |Cite
|
Sign up to set email alerts
|

Child abuse in 28 developing and transitional countries--results from the Multiple Indicator Cluster Surveys

Abstract: Child abuse is a very common phenomenon in many of the countries examined. We found substantial variations in prevalence across countries and regions, with the highest prevalence in African countries. Population-based interventions (e.g. educational programmes) should be undertaken to increase public awareness of this problem. Actions on changing parental attitudes towards corporal punishment of children may help to prevent child abuse. The specific local situation in each country should be considered when sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
165
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(190 citation statements)
references
References 30 publications
21
165
3
1
Order By: Relevance
“…We contend that it is plausible that such knowledge, as well as a better recognition and application of the measures that women deem effective to meet their needs given their particular social and societal contexts, could contribute to the prevention of intergenerational transmission of abuse. Interestingly enough, while the measures proposed by Akmatov (2011) and Pinheiro (2006) focus specifically on the international prevention of child maltreatment in low-and middle-income countries, these authors advocated for recommendations that are similar to those that Canadian women have made to support their reweaving work. These include, for example, the need to develop programs that account for specific local limitations (i.e., socioeconomic, educational; Akmatov, 2011), the prioritization of prevention, the promotion of nonviolent values in society and in practice contexts, awareness-raising against stereotypical gender roles and discrimination, the enhancement of the capacity of those who work with and for children, the provision of recovery and social reintegration services, and the participation of children (Pinheiro, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We contend that it is plausible that such knowledge, as well as a better recognition and application of the measures that women deem effective to meet their needs given their particular social and societal contexts, could contribute to the prevention of intergenerational transmission of abuse. Interestingly enough, while the measures proposed by Akmatov (2011) and Pinheiro (2006) focus specifically on the international prevention of child maltreatment in low-and middle-income countries, these authors advocated for recommendations that are similar to those that Canadian women have made to support their reweaving work. These include, for example, the need to develop programs that account for specific local limitations (i.e., socioeconomic, educational; Akmatov, 2011), the prioritization of prevention, the promotion of nonviolent values in society and in practice contexts, awareness-raising against stereotypical gender roles and discrimination, the enhancement of the capacity of those who work with and for children, the provision of recovery and social reintegration services, and the participation of children (Pinheiro, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Women's ability to reweave, however, was facilitated or challenged through intersections with family, networks, single stories, and prescribed rules and routines. We propose that reweaving work is a significant phenomenon to consider as deeper understandings of the dynamic experience of adult resilience are sought.Child maltreatment, a designation used to identify all types of physical, sexual, and emotional violence threatening children's development, health, survival, and dignity, is a problem of global magnitude (Akmatov, 2011;Pinheiro, 2006; World Health Organization [WHO], 2010). It is a phenomenon that is difficult to study, however, as these childhood violence experiences most often occur out of sight, at the hands of adults known to children (i.e., parents, relatives, teachers, coaches, church members), and under conditions of fear and enforced silence (Akmatov…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 A review of data from 28 LMICs revealed that 83% of children were being psychologically abused and that 43% were severely physically abused. 5 Besides sociodemographic and cultural factors, poor parenting practices are important determinants for child maltreatment. 6,7 A recent qualitative study of abused children reported negative perceptions associated with poor parenting practices including aggressive or inconsistent disciplinary styles, neglectful behaviors, authoritative decision-making, and failure to set appropriate boundaries.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the Multiple Indicator Cluster Surveys data from 28 countries shows that 43% of children aged 2-14 years in African countries, and 9% in 'transitional' states, have experienced severe physical violence from caregivers. 1 There are a host of negative health and social consequences associated with exposure to physical violence in childhood, especially during this early period. These include increased risk of depressive disorders and suicide attempts, 2 poor educational attainment 3 and increased risk of perpetrating or experiencing intimate partner violence in later relationships.…”
mentioning
confidence: 99%